Massive Apoptosis of Thymocytes in T-Cell-Deficient Id1 Transgenic Mice - Kim, Dongsoo (American Society for Microbiology, 1999)
Id1 is an inhibitor of a group of basic helix-loop-helix transcription factors, collectively called E proteins, which includes E12, E47, E2-2, and HEB. We have generated transgenic mice in which Id1 is specifically expressed in T cells. The total number of thymocytes in these mice is less than 4% of that in wild-type mice. The majority of the transgenic thymocytes are CD4 and CD8 double negative and bear the cell surface markers of multipotent progenitor cells. A small number of thymocytes, however, differentiate into CD4 or CD8 single-positive T cells, which also display different characteristics from their wild-type counterparts. More importantly, apoptotic cells constitute about 50% of the total thymocytes. These apoptotic thymocytes have rearranged their T-cell receptor genes, suggesting that they are differentiating T cells. This finding has raised the possibility that the T-cell deficiency in Id1 transgenic mice is the result of a massive apoptosis of differentiating T cells triggered by Id1 expression as opposed to a developmental block at the earliest progenitor stage. The progenitor cells accumulated in the transgenic mice might have survived because they are not susceptible to the apoptotic signals. Despite the massive cell death of the thymocytes at young ages, Id1 transgenic mice frequently develop T-cell lymphoma later in their life span, and lymphomagenesis appears to occur at different stages of T-cell development. Taken together, our data suggest that E proteins, being the targets of Id1, are essential regulators for normal T-cell differentiation and tumor suppression.